Glycemic Management in the Bariatric Surgery Population: A Review of the Literature. Issue 6 (21st June 2018) - Howard, Meredith L.; Steuber, Taylor D.; Nisly, Sarah A.
Abstract : Obesity is a worldwide epidemic often complicated by multiple comorbidities, including type 2 diabetes mellitus (T2DM). Bariatric surgery is an increasingly common and effective weight‐loss strategy for obese patients that may result in resolution of metabolic‐related disease states, such as T2DM. Although bariatric surgery has many positive outcomes for patients, dietary and pathophysiologic changes can create difficult‐to‐control blood glucose, especially in the immediate perioperative setting. Depending on oral antidiabetic agent and insulin needs preoperatively, many patients require cessation of oral agents and reduction or cessation of insulin. Unfortunately, despite available perioperative bariatric surgery guidelines, no specific recommendations for perioperative oral antidiabetic agent or insulin management exist. The purpose of this article is to review the current body of evidence for blood glucose management in the setting of bariatric surgery. An English‐language PubMed and MEDLINE search was conducted from 1964 through March 2018 using the following search terms alone and in various combinations: bariatric surgery, gastric banding, laparoscopic sleeve gastrectomy (LSG), Roux‐en‐Y gastric bypass (RYGB), glucose management, insulin, and oral antidiabetic agent . Five articles were identified evaluating insulin management in the perioperative bariatric surgery setting, which were separated into two categories: immediate perioperative insulin management and long‐term postoperative insulin management. Overall, various blood glucose management insulin protocols were evaluated. All studies included some type of insulin reduction in the perioperative setting. No studies identified specifically evaluated down‐titration or discontinuation of oral antidiabetic agents. Given the lack of specific guideline recommendations, limitations of standardized insulin protocols, and inconsistency of outcomes studied, perioperative insulin at reduced doses compared to previous maintenance doses coupled with frequent blood glucose monitoring is reasonable. An opportunity exists for successful protocols to be addressed in future, larger studies.